The Effect of Vermicompost and Spraying with Humic Acid and Fertilizer on Quantitative and Qualitative Characteristics of Rosemary - Jalayerinia, Niloufar; Kalat, Seyed Mohsen Nabavi; Haghighi, Reza Sadr abadi (Asian Journal of Biological and Life Sciences, 2017)
Rosemary (Rosmarinus officinalis L.) is an evergreen woody aromatic herb with a characteristic aroma and lavender-like leaves. This research was conducted to evaluate the effect of vermicompost and foliar application of humic acid and complete fertilizer on quantitative and qualitative characteristics of rosemary in the first and second harvest. This study was laid out in factorial experiment with randomized completely design (RCD) with three replications in greenhouse condition. Treatments included vermicompost (0, 4, 8 and 12 weight percentage of pot soil) and foliar application in four levels (no spray, sprayed with fertilizer, foliar application of human acid, foliar spray with fertilizer and humid acid), respectively. The characteristics such as plant height, the number of branches, leaves and flowers per plant, fresh and dry weight of shoots and essential oil content were measured. The results showed that different levels of vermicompost on the first and second harvest was significant. In addition, all traits were significantly affected by different levels in both harvest. With increasing vermicompost level all quantitative and qualitative traits increased significantly. The highest values for all traits in both first and second harvest obtained in combination of humic acid and complete fertilizer.